Анализ эффективности энергетических систем на основе возобновляемых источников энергии - Антипов, Е. А.; Мартынюк, Л. В.; Воронцов, Я. С. (Енергетика і автоматика, 2017)
UDC 621.1.016:620.97(075.8) ANALYSIS OF EFFICIENCY OF ENERGY SYSTEMS BASED ON RENEWABLE SOURCES OF ENERGY I. ANTYPOV, L. MARTYNYUK, J. VORONTSOV Introduction. The limited traditional fuel and energy resources (gaseous, liquid and solid fuels), the constant increase in prices for them, as well as the negative impact of their combustion products on the environment, indicate the need for more rational use of them, which can be achieved both through the use of modern energy-saving equipment, and by creating energy supply systems for consumers using renewable energy sources. Analysis of recent researches and publications. Given the wide variety of renewable energy equipment (wind generators, photovoltaic cells, solar collectors, batteries, etc.), it is possible to develop a variety of energy systems different in the combination of primary energy sources. However, the low flux density of renewable energy and the inability to regulate its supply regimes do not allow us to focus the development of energy exclusively on renewable energy sources (RES). Therefore, the most eco-nomically effective are the options of joint application of traditional energy resources and renewable energy sources as part of a single system for obtaining thermal and electrical energy. Purpose. Solve the task of energy and economic optimization of the energy supply system for the municipal consumer using renewable energy sources. Methods. We will give the basis for exergoeconomic optimization and formulate the concept of exergy. The concept of exergy as the maximum working capacity is convenient to use when considering the degree of perfection of various processes in terms of energy conversion. If the process proceeds completely reversibly, then the resulting total operability of the substance (the same applies to mechanical work) should be equal to the expended work capacity. In the presence of irreversibility, a decrease in efficiency is a loss of energy. It is expedient to carry out an exergetic economic evaluation at the level of system components [3-6]. Exergoeconomics has specific terminology. Variables are usually taken to mean quantities that can be changed for optimization purposes. More often thermodynamic quantities appear in the form of variables. By fuel is meant any flow entering the component. A special case is a component in which the fuel component is fuel for the entire system. Streams emerging from the component can (in general) represent: product - the flow that is sent from the component under consideration to the next, for which it will be fuel; destruction of exergy, in a component is associated with capital and operational costs associated with the component’s time; loss exergy, which are observed when considering the conditions of interaction of the component with the environment. The formulated optimization problem represents a multi-extremal problem of discrete nonlinear programming complicated by constraints.. Results. Using this technique, we calculate the magnitude of the exergoeconomic factor for the main types of energy supply systems for consumers from renewable sources, for example, with a power of 20 kW. As a result, the most effective energy supply systems from renewable energy sources are photoelectric and heat pump, the exergo-economic factor of which, in comparison with the use of electric energy, is respectively 0.32 and 0.521 cu. Discussion. Consideration of the general principles of exergoeconomic optimization of renewable energy systems and their comparison with traditional energy sources allows us to state the following: 1. At present, in small autonomous energy complexes, the options for joint use of traditional energy resources and renewable energy are most economically effective. 2. Objective function (in monetary units) at the project stage is an expense that involves the use of market prices for products received from the system, and can be minimized (income is maximized), except the technical improvement of the system. 3. In the task of minimizing the cost of the energy system, the following are involved: thermodynamics, design and production, the economy, each of which has its own methods of forming the given values and is represented by the corresponding models. 4. In the transition to heterogeneous linear systems, the prevailing method of searching for the optimal variant is almost completely preserved. 5. The most effective energy supply systems from renewable energy sources are photoelectric and heat pump, the exergo-economic factor of which, in comparison with the use of electric energy, is respectively 0.32 and 0.521 cu.